Marine migratory behavior of anadromous brown trout and Arctic char in a Norwegian fjord system - Halvorsen, Andrine Emilie (2019)
Brown trout (BT) and Arctic char (AC) are freshwater species exhibiting a wide array of life history and migration strategies. Populations with free access to the marine environment often display anadromous tendencies, with some individuals undertaking feeding migrations to sea. Recent decades have seen a general decline in anadromous populations of both species across Europe, possibly a consequence of increased marine mortality due to deteriorating conditions at sea. This study aims to increase the knowledge concerning marine migratory behavior of anadromous brown trout and Arctic char through studies of sympatric populations in a fjord system in northern Norway. Acoustic telemetry was used to track the migrations of individual fish (AC: n = 54, LT = 270-480 mm; BT: n = 111, LT = 169-880 mm) and stable isotope analysis was used to identify important prey groups for each species in connection to the marine migration phase (AC: n = 26, LT = 204-390 mm; BT: n = 110, LT = 185-720 mm). Fish were followed in the fjord in 2016, 2017 and 2018. Downstream migration typically occurred in either May or June, with clear differences observed between the species. In 2017, brown trout migrated downstream earlier (median day = 28.05) and displayed greater individual variation on migration timing (interquartile range, IQR = 12 days) than Arctic char (median day = 07.06, IQR = 1.75 days). Timing of marine entry coincided with increased river discharge for Arctic char, but not for brown trout. Brown trout downstream migration timing was negatively correlated with fish body size (LT). Duration of the marine migration was greater for brown trout than for Arctic char, although large individual variation was observed for both species (AC: mean average = 49.1 ± 32.4 days; BT: mean average = 60.7 ± 31.7 days). For brown trout, migration duration was negatively correlated with Julian day of entry into the fjord. Brown trout utilized the entire fjord system, and had a greater proportion of long-distance migrants than Arctic char (BT = 65.0%; AC = 28.6%), suggested to be caused by differences in prey choice and spatial distribution of the preferred prey groups. Arctic char mostly utilized the inner fjord areas, and remained in closer proximity to the estuary throughout the marine migration. Stable isotope analysis revealed high proportions of freshwater invertebrates in the diet of Arctic char, suggesting that feeding likely occurred partly in the estuary. Brown trout had mainly been feeding on marine fish and shrimp. The results from this study suggest that Arctic char and brown trout have different marine migratory strategies, driven in part by differences in feeding preferences. However, a significant size difference between the two species is likely to have contributed to some the differences observed in the present study.